ABOUT THE SOCIALIZATION OF LABOR AND INCREASE OF SAFETY - I. Matskulyak; U. Aliyev; D. Matskulyak; N. Naghdaliyev (Вестник университета, 2016)
A number of aspects of socialization of labor and safety in domestic conditions are revealed in the article, which conceptual bases are based on scientific, standard and empirical levels. The social principles-imperatives and their role in increase of socialization of labor and safety and also neoliberal, conservative and social and democratic social models of the state are considered. The dual character of labor socialization is established as a condition and a source of financing of the public social expenditures and as the instrument of regulation of the social and economic safe relations.